Comparative regional protection frameworks for refugees: norms and norm entrepreneurs. Issue 2 (17th February 2016) - Kneebone, Susan
Abstract : This article analyses the strengths and limits of regional approaches to refugee protection. It compares three regions; namely the EU, Latin America and the Southeast Asian (SEA) region. It refers to two refugee protection crises to highlight the importance of regional approaches to refugee protection: namely the Rohingya "boat people" crisis which unfolded in the Indian Ocean in May 2015 and the advance of Syrian refugees towards Europe which escalated from the same period. It identifies the norms of refugee protection which have been "internalised" in the three regional contexts and contextualises the regional processes. It argues for the importance of looking closely at the underlying norms, and the identities and activities of the relevant "norm entrepreneurs" at the regional level. It concludes that regional solutions for refugee protection will be most effective when the norms have been solidly embedded in legal systems and institutions.